2007
DOI: 10.1086/513735
|View full text |Cite
|
Sign up to set email alerts
|

ASpitzer Space TelescopeStudy of Disks in the Young σ Orionis Cluster

Abstract: We report new Spitzer Space Telescope observations from the IRAC and MIPS instruments of the young (∼ 3 Myr) σ Orionis cluster. The populous nature of this cluster makes it a good target for statistically-significant studies of disk emission as a function of mass. We identify 336 stars as members of the cluster using optical and near-infrared color magnitude diagrams. Using the spectral energy distribution (SED) slopes in the IRAC spectral range, we place objects in several classes: non-excess stars, stars wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
633
9
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(688 citation statements)
references
References 72 publications
45
633
9
1
Order By: Relevance
“…For the full PCM population in the ACIS FOV (Figure 6 Our Chandra observation of M17 SWex has identified a substantial population of very young IMPS with no IR excess. Clearly the inner disk lifetime for IMPS is shorter than the inner disk lifetime of~3 Myr for low-mass T Tauri stars, as numerous previous studies have reported (Hillenbrand et al 1992;Haisch et al 2001;Hernández et al 2007;Roccatagliata et al 2011). PW10 parameterized the disk lifetime t m d ( ) for IMPS in terms of a disk fraction with a power-law mass dependence,…”
Section: Total Stellar Populationmentioning
confidence: 99%
“…For the full PCM population in the ACIS FOV (Figure 6 Our Chandra observation of M17 SWex has identified a substantial population of very young IMPS with no IR excess. Clearly the inner disk lifetime for IMPS is shorter than the inner disk lifetime of~3 Myr for low-mass T Tauri stars, as numerous previous studies have reported (Hillenbrand et al 1992;Haisch et al 2001;Hernández et al 2007;Roccatagliata et al 2011). PW10 parameterized the disk lifetime t m d ( ) for IMPS in terms of a disk fraction with a power-law mass dependence,…”
Section: Total Stellar Populationmentioning
confidence: 99%
“…For our new candidates (see Sect. 4), we have obtained the Spitzer photometry following the procedure described in Zapatero Osorio et al (2007) and using the data published by Hernández et al (2007) and Scholz & Jayawardhana (2008). A comparison of these two data sets is provided in Luhman et al (2008, see e.g.…”
Section: Near-and Mid-infrared Datamentioning
confidence: 99%
“…For example, the bright (in the infrared) giant star IRAS 05358-0238 was once classified as a Class I object in the σ Orionis cluster (Oliveira & van Loon 2004;Hernández et al 2007;Caballero 2008). Since the surveyed area in this work is rich in star-forming regions (including σ Orionis), we had to be careful with disentangling both pre-main sequence and giant star populations.…”
Section: Variable Background Giantsmentioning
confidence: 99%